The influence of pH on the in vitro permeation of rhodium through human skin - Jansen Van Rensburg, Sané; Franken, Anja; Du Plessis, Jeanetta; Du Plessis, Johannes Lodewykus (Toxicology and industrial health, 2017)
Workers in precious metals refineries are at risk of exposure to salt compounds of the platinum group metals through inhalation, as well as through the skin. Rhodium salt permeation through the skin has previously been proven using rhodium trichloride (RhCl ) dissolved in synthetic sweat at a pH of 6.5. However, the skin surface pH of refinery workers may be lower than 6.5. The aim of this study was to investigate the influence of pH 6.5 and 4.5 on the in vitro permeation of rhodium through intact Caucasian skin using Franz diffusion cells. A concentration of 0.3 mg mL rhodium was used and analyses were performed using inductively coupled plasma mass spectrometry and inductively coupled plasma optical emission spectrometry. Results indicated a cumulative increase in permeation over 24 h. Rhodium permeation after 12 h was significantly greater at pH 4.5 (1.56 ± 0.24 ng cm ) than at 6.5 (0.85 ± 0.13 ng cm ; p = 0.02). At both pH levels, there was a highly significant difference ( p < 0.01) between the mass of rhodium remaining in the skin (1428.68 ± 224.67 ng cm at pH 4.5 and 1029.90 ± 115.96 ng cm at pH 6.5) and the mass that diffused through (0.88 ± 0.17 ng cm at pH 4.5 and 0.62 ± 0.10 ng cm at pH 6.5). From these findings, it is evident that an acidic working environment or low skin surface pH may enhance permeation of rhodium salts, contributing to sensitization and adverse health effects.